Inefficient but effective? A field experiment on the effectiveness of direct and indirect transfer mechanism - Hannes Koppel; Günther G. Schulze (Philipps-University Marburg, Faculty of Business Administration and Economics, 2008)
We conduct a field experiment on direct and indirect transfer mechanisms. It shows that people are willing to donate significantly more if the donation is indirect, i.e., it is tied to the purchase of a good with a price premium, rather than made directly. This points to an efficiencyeffectiveness tradeoff even though indirect donations are less efficient than direct donations, they are more effective in mobilizing resources. Our findings hold for Fair Trade coffee as well as for normal coffee. However, the strength of the efficiencyeffectiveness tradeoff is higher in the case of Fair Trade.
Keywords: C93; D63; D64; H21; H41; 330; Tied transfers; donations; charity; efficiency versus effectiveness; fair trade